2006
DOI: 10.1038/ja.2006.3
|View full text |Cite
|
Sign up to set email alerts
|

A New Teleocidin Analog from Streptomyces sp. MM216-87F4 Induces Substance P Release from Rat Dorsal Root Ganglion Neurons

Abstract: A new teleocidin analog was isolated from the fermentation medium of Streptomyces sp. MM216-87F4 and its structure was elucidated as 14-O-(Nacetylglucosaminyl) teleocidin A (GlcNAc-TA). GlcNAc-TA induces the translocation of protein kinases Ca and q fused with enhanced green fluorescent protein (PKCa -EGFP and PKCq -EGFP) to the plasma membrane in stable transfectants, and reduces intracellular calcium mobilization induced by agonists of G-protein coupled receptors in various cell lines without causing irritat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 13 publications
(15 reference statements)
0
4
0
Order By: Relevance
“…Miscellaneous peptides that lack anti-infective related activity are summarized herein. These include aeruginosides, 1113 aeruginosins, 1114 muraceins, 1115 enkastines, 1116 banyasides, 1117 phosphoramidon, 1118 GlcNAc-TA, 1119 mycothiols, 47,1120 bacillithiols, 1121 and alanopine 1122 from Streptomyces , Nostoc , Nocardia , Planktothrix , Bacillus , Staphylococcus Providencia , Proteus and Oscillatoria (Fig. 51).…”
Section: Peptidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Miscellaneous peptides that lack anti-infective related activity are summarized herein. These include aeruginosides, 1113 aeruginosins, 1114 muraceins, 1115 enkastines, 1116 banyasides, 1117 phosphoramidon, 1118 GlcNAc-TA, 1119 mycothiols, 47,1120 bacillithiols, 1121 and alanopine 1122 from Streptomyces , Nostoc , Nocardia , Planktothrix , Bacillus , Staphylococcus Providencia , Proteus and Oscillatoria (Fig. 51).…”
Section: Peptidesmentioning
confidence: 99%
“…1118 GlcNAc-TA is a prenylated indolactam C-14- O -glycoside ( N -acetyl-β- d -glucosamine, 153 ). 1119 This is the only naturally-occurring teleocidin glycoside and is a small molecule activator of protein kinase C and induces the release of excitatory neuropeptides.…”
Section: Peptidesmentioning
confidence: 99%
“…The teleocidin analog 14- O -( N -acetylglucosaminyl) teleocidin A (GlcNAc-TA) ( 447 ) was isolated from Streptomyces sp. MM216-87F4 and was shown to affect the release of the neurotransmitter substance P from Dorsal Root Ganglia (DRG) neurons via protein kinase C (PKC) pathway ( Figure 72 ) [ 191 ]. JBIR-31 ( 448 ) was isolated from Streptomyces sp.…”
Section: Marine Indole Alkaloidsmentioning
confidence: 99%
“…32 Recently, it has been reported that a teleocidin derivative, 14-O-(N-acetylglucosaminyl) teleocidin A, induces the translocation of protein kinases Ca and y, and sensitizes the release of excitatory neuropeptide substance P induced by capsaicin from primary-cultured dorsal root ganglion neurons of the rat. 33 Because teleocidin analogs possess various biological activities, studies on detailed biological activities against MPM cells by 1 and teleocidin A 1 are now underway.…”
mentioning
confidence: 99%